PERCOBAAN FRAKSIONASI-DISTILASI MINYAK TERPENTIN DARI PINUS MERKUSII JUNG ET DE VRIESE - Bambang Wiyono; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Turpentine oil was optained from rosin factory in Paninggaran, Central Java, and Sukun, East Java. Both samples were separated by fractional distilation into several fractions. The distilling was conducted at boiling temperature with atmospheric pressure. The boiling point ranges were 156 - 164°C for the first fraction; 164 - 167°C for the second fraction; 167 - 170° C for the third fraction; and 170° C and upward for the residual fraction.The results indicated that the amount of turpentine fractions from Paninggaran and Sukun were consecutively 73.60% and 70.0% of first fraction: 1340% and 15.80% of second fraction; 3.17% and 3.79% of third fraction; and 9.97% and 9.86% of the residual. Based on the boiling temperature of each component, the first fraction is assumed to contain n-heptane, p-thujene, a-pinene, and camphene; β-pinene and myrcene in the second fraction; myrcene, β-phellandrene, and ∆3-carene in the third fraction; and the residual fraction contains, β-phellandrene. ∆3-carene, p-cymene, limonene, ά-and ɤ-terpinene, etc. The major components of turpentine oil are ά-and β-pinene. These components can be obtained by decreasing the boiling range to 154 - 158° C for ά-pinene and 164 - 166° C for β-pinene. The fractional distillation with these temperatures is expected to increase the utilization of turpentine as raw material for synthetic pine oil, perfumery, etc.